KERJASAMA DINAS PERHUBUNGAN DAN DINAS SOSIAL DALAM PENGADAAN FASILITAS TRANSPORTASI PUBLIK DARAT(TRANSJAKARTA) BAGI PENYANDANG DISABILITAS DI PROVINSI DKI JAKARTA - DEWI, TRIA NURWARA (Jurnal Administrasi Publik, 2016)
Abstract:Cooperation between the Department of Transportation and Departmen of Social Welfare in the Procurement Facility for Land Public Transportation (Transjakarta) for Persons with Disabilities in DKI Jakarta. DKI Jakarta is know as the busiest city, so that the society with high degree of mobility needs transportation services, person with disabilities are not expection. Transportation which has been providing facilities for person with disabilities of Transjakarta. The purpose of this study is to investigate and describe the forms of cooperation of department, the actors involved in the procurement of Transjakarta for disabilities, the result of the cooperation, supporting and inhibiting factors of cooperation of Department of Transportation and Department of Social Welare. Based on the result o the study, it show thet the procurement facilities of land public transportation (Transjakarta) for person with disabilities in Jakarta is already performing well. Stakeholders have been carrying out the rule nicely. Generating a Regulation No 10 o 2011 on the Protection o Person with Disabilities. Keywords: cooperation, transjakarta, disabilities, DKI Jakarta Abstrak: Kerjasama Dinas Perhubungan dan Dinas Sosial dalam Pengadaan Fasilitas Transportasi Publik Darat (Transjakarta) bagi Penyandang Disabilitas di Provinsi DKI Jakarta. Provinsi DKI Jakarta sebagai kota sibuk sehingga mobilitas masyarakatnya yang tinggi membutuhkan pelayanan transportasi, tidak terkecuali penyandang disabilitas. Transportasi yang telah menyediaakan fasilitas bagi disabilitas adalah Transjakarta. Tujuan dari penelitian ini adalah untuk mengetahui dan mendeskripsikan bentuk kerjasama, aktor yang terlibat dalam pengadaan fasilitas Transjakarta bagi penyandang disabilitas, hasil kerjasama, faktor pendukung dan penghambat kerjasama Dinas Perhubungan dan Dinas Sosial. Hasil penelitian ini menunjukkan dalam pengadaan fasilitas transportasi publik darat (Transjakarta) bagi penyandang disabilitas di Provinsi DKI Jakarta sudah terlaksana dengan baik. Aktor yang terlibat sudah melaksanakan peran dengan baik. Serta, menghasilkan Peraturan Daerah DKI Jakarta Nomor 10 Tahun 2011 tentang Perlindungan Penyandang Disabilitas. Â  Kata kunci:kerjasama, transjakarta, disabilitas, DKI Jakarta.